A study of obesity among health staff at Kulaijaya District Health Department - Shalihin, Mohd Shaiful Ehsan; Poh, Lin Chin; , Misringaton (Jabatan Kesihatan Negeri Johor, 2012)
OBJECTIVE: To study and report prevalence of among health staff at Kulaijaya District Health Department and describe their association with gender, marital status, respective job scope and working environment, using standardized international definitions. METHODS: This cross sectional study studied body mass index of all the health staff of Kulaijaya Health Department except expectant mothers and females in their first three months postpartum period. Body mass index (BMI:kg/m2) was calculated from measured weight and height, using calibrated weighing scales and body meters. Body weight classifications were defined as follows: According to WHO Expert Consultation 2004 for Asian BMI: underweight (BMI < 18.5), normal weight (18.5 to 24.9), pre- /overweight (BMI 25.0-29.9), e (BMI > or = 30.0). Otherwise, 100% respondent's rate was achieved. Descriptive and correlation analysis were performed using SPSS version 15. A significance level of p-value less than or equal to 0.05 was considered statistically s i g n i f i c a n t ( p < 0 . 0 5 ) . RESULTS: The prevalence were found to be 5.8% for underweight (CI 0.03-0.10), 40.2% for normal BMI (CI 0.33-0.47), 33.9% for overweight (CI 0.27-0.41) and 20.1% for obese (CI 0.14-0.26). Higher prevalence of obesity was found in males (20.1%) (CI 0.13-0.32), those confined in office settings (23.3%) (CI 0.14-0.35) and in married employees (20.6%) (CI 0.15-0.27). There was a significant association between marital status and overweight (P 0.023). Among all job scopes, medical doctors had the highest prevalence of obesity (38.5%) (0.18-0.64). Prevalence of normal weight and underweight are higher in those working in clinical setting (46.5%)(CI 0.38-0.55) compared to office staff ( 4 5 . 0 % ) ( C I 0 . 3 3 - 0 . 5 8 ) . CONCLUSION: There was higher prevalence of obesity and overweight amongst male staff, office and inspectorate personnel and medical officers at Kulaijaya District Health Department in relation to national and state figures. Regular weight management program should be implemented to all staff regardless of gender, marital status, job scope and working environment.